2018
DOI: 10.1002/cncr.31288
|View full text |Cite
|
Sign up to set email alerts
|

Patient Protection and Affordable Care Act Medicaid expansion and gains in health insurance coverage and access among cancer survivors

Abstract: The results of the current study suggest that the Patient Protection and Affordable Care Act Medicaid expansion has improved coverage and access for cancer survivors. Cancer 2018;124:2645-52. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Overall, the percentage uninsured among cancer survivors decreased from 12.8% pre‐ACA to 6.0% post‐ACA in expansion states and decreased from 18.2% pre‐ACA to 13.4% post‐ACA in nonexpansion states, with a 1.8‐ppt net decrease associated with Medicaid expansion 92 . Similar findings were reported elsewhere, with greater declines in the percentage uninsured among low‐income cancer survivors 93 …”
Section: Overview Of Research Addressing the Aca And Cancer Caresupporting
confidence: 81%
“…Overall, the percentage uninsured among cancer survivors decreased from 12.8% pre‐ACA to 6.0% post‐ACA in expansion states and decreased from 18.2% pre‐ACA to 13.4% post‐ACA in nonexpansion states, with a 1.8‐ppt net decrease associated with Medicaid expansion 92 . Similar findings were reported elsewhere, with greater declines in the percentage uninsured among low‐income cancer survivors 93 …”
Section: Overview Of Research Addressing the Aca And Cancer Caresupporting
confidence: 81%
“…Studies conducted before the 2010 Affordable Care Act reported that financial burden created worry and anger when tools for lymphedema management were not covered by insurance [ 40 ]. The present study suggests that these challenges persist even after the Affordable Care Act, which has the potential to expand health insurance coverage for cancer-related care [ 41 ] and for cancer survivors [ 42 , 43 ]. For women cancer survivors with lymphedema, who continued to manage a disease long after completing cancer treatment, these challenges persisted due to ongoing needs for lymphedema care.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the authors found that Medicaid expansion was associated with a reduction in the number of uninsured and the increased likelihood of having a personal physician. Individuals residing in expansion states fared considerably better than those in the nonexpansion states . Davidoff et al.…”
Section: Impact Of the Ppacamentioning
confidence: 99%
“…Nikpay et al. also using data from the BRFSS, explored the impact of Medicaid expansion on cancer survivors . Overall, the authors found that Medicaid expansion was associated with a reduction in the number of uninsured and the increased likelihood of having a personal physician.…”
Section: Impact Of the Ppacamentioning
confidence: 99%
See 1 more Smart Citation